A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China - Li, Weihai; Mo, Raorao; Yang, Ding (Zootaxa, 2019)
A complementary description of Kyphopteryx yangi Du & Chen, 2019 is presented based on a recently collected topotype male. Taxonomic features of this male are compared with the holotype.